2020
DOI: 10.3390/ma13183925
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and Bioactivity of Set Direct Pulp Capping Materials on Human Dental Pulp Stem Cells

Abstract: In this study, we assessed the biocompatibility and bioactivity of various pulp capping materials—ProRoot MTA (Dentsply Tulsa Dental Specialties), Biodentine (Septodont), TheraCal LC (Bisco), and Dycal (Dentsply Caulk)—on human dental pulp stem cells (hDPSCs). Experimental disks (diameter, 7 mm; height, 4 mm) were stored in a humified incubator at 37 °C for 48 h. Then, the pulp capping materials were tested for cytotoxic effects by methyl-thiazoldiphenyl-tetrazolium and scratch wound healing assays, and for mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 35 publications
4
21
1
Order By: Relevance
“…This is due to the formation of CH following the hydration reaction, which created the premise of a high pH with antibacterial activity and the formation of calcium ions that induced morpho-differentiation and proliferation of odontoblast-like cells at the level of pulp exposure site [ 148 ]. Even though TheraCal LC contains resin in its composition, and there is a risk of remaining unpolymerized resin monomers, it has good biocompatibility compared to CH [ 149 ]. However, one study indicated that after 72 h, TheraCal LC showed a decrease in the percentage of cell viability, similar to CH [ 150 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the formation of CH following the hydration reaction, which created the premise of a high pH with antibacterial activity and the formation of calcium ions that induced morpho-differentiation and proliferation of odontoblast-like cells at the level of pulp exposure site [ 148 ]. Even though TheraCal LC contains resin in its composition, and there is a risk of remaining unpolymerized resin monomers, it has good biocompatibility compared to CH [ 149 ]. However, one study indicated that after 72 h, TheraCal LC showed a decrease in the percentage of cell viability, similar to CH [ 150 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipski et al, reported that Biodentine had an 82% success rate at 1–1.5 years after direct pulp capping, and the success rate was 90.0% among patients under 40 years of age [ 26 ]. Biodentine was associated with higher cell proliferation and migration rates than the rates observed with other pulp-capping materials [ 18 , 27 , 28 ]. The effects of Biodentine on dentin bridge formation were similar to those observed with ProRoot MTA [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hDPSC line was established at Top Cell Bio, Inc (Seoul, Korea). The experiments were performed with hDPSCs that had been passaged 4 times, as described previously [ 18 ]. Cells were grown in HyClone Minimum Essential Medium (α-MEM; GE Healthcare Life Sciences, Pittsburgh, PA, USA) supplemented with HyClone 10% fetal bovine serum (GE Healthcare Life Sciences), 100 U/mL penicillin, and 100 μg/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained when hDPSCs were cultured in medium conditioned with Biodentine or ProRoot MTA 47 . When transwell membrane was used to avoid direct contact between the biomaterials and hDPSCs, there was no significant difference in cell viability and cell migration between ProRoot MTA and Biodentine 48 .…”
Section: Discussionmentioning
confidence: 99%